2019
DOI: 10.1111/are.13981
|View full text |Cite
|
Sign up to set email alerts
|

Regulations on glucose metabolism affected by dietary carbohydrate in different strains of juvenile gibel carp (Carassius gibelio)

Abstract: This experiment was conducted to study the effects of dietary carbohydrate on glucose metabolism in gibel carp (Carassius gibelio) as well to investigate if different clones had different responses to carbohydrate intake. Unselected Dongting strain (DT strain), selected gibel carp “CAS III” (A strain) and gibel carp “CAS V” (F strain) were fed with no corn starch diet (0C), 30% corn starch diet (30C) and 45% corn starch diet (45C) for 8 weeks. The results showed that selected F strain showed higher growth perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 39 publications
7
7
0
Order By: Relevance
“…However, strain F starved for 38 and 77 days exhibited lower expression levels. Previous results showed that strain A had higher gene expression levels of pk than strain F when the fish were fed diets containing different levels of carbohydrate or lipid (25,26). In the present study, strain A still presented higher pk mRNA levels than strain F under starvation during winter.…”
Section: Interactions Between Strain and Starvation Periodsupporting
confidence: 46%
See 3 more Smart Citations
“…However, strain F starved for 38 and 77 days exhibited lower expression levels. Previous results showed that strain A had higher gene expression levels of pk than strain F when the fish were fed diets containing different levels of carbohydrate or lipid (25,26). In the present study, strain A still presented higher pk mRNA levels than strain F under starvation during winter.…”
Section: Interactions Between Strain and Starvation Periodsupporting
confidence: 46%
“…Strain A had lower plasma glucose levels but higher liver glycogen contents and higher mRNA levels of fbpase and pepck than strain F. The previous results showed that these two strains had no significant differences in mRNA of fbpase or pepck when fed different diets (25,26). Therefore, we suggested that strain A and strain F might have different responses in glucose metabolism to starvation and low temperature.…”
Section: Different Physiological Responses To Fasting In Overwinterinmentioning
confidence: 70%
See 2 more Smart Citations
“…However, even in species with similar nutritional requirements, there are morphological and physiological differences that change digestive and absorption speed (Kamalam et al, ) and affect animal performance. Therefore, monomeric composition and degree of carbohydrate polymerization must also be considered for diet composition, since metabolic utilization and net energy value of simple sugars and complex polysaccharides appear to be dependent on fish species (Song et al, ). In general, apparent digestibility and intestinal uptake decrease with increased complexity (glucose > dextrin > starch).…”
Section: Introductionmentioning
confidence: 99%